Health-related quality of life in postmenopausal women with low BMD with or without prevalent vertebral fractures. - Oleksik, A; Lips, P; Dawson, A; Minshall, M; Shen, W; Cooper, C; Kanis, J (2000)
Fractures and subsequent morbidity determine the impact of established postmenopausal osteoporosis. Health-related quality of life (HRQOL) has become an important outcome criterion in the assessment and follow-up of osteoporotic patients. As part of the baseline measurements of the Multiple Outcomes of Raloxifene Evaluation (MORE) study, HRQOL was assessed in 751 osteoporotic (bone mineral density [BMD] T score > or = -2.5) women from Europe with or without vertebral fractures (VFX). This was done using the quality of life questionnaire of the European Foundation for Osteoporosis (QUALEFFO), Nottingham Health Profile (NHP) and the EQ-5D (former EuroQol). QUALEFFO contains questions in five domains: pain, physical function, social function, general health perception, and mental function. Each domain score and QUALEFFO total scores are expressed on a 100-point scale, with 0 corresponding to the best HRQOL. In comparison with patients without VFX, those with VFX were older (66.2 +/- 5.9 years vs. 68.8 +/- 6.3 years; p < 0.001), had higher prevalence of nonvertebral fractures (25% vs. 36%; p = 0.002), and higher QUALEFFO scores (worse HRQOL; total score, 26 +/- 14 vs. 36 +/- 17; p < 0.001). QUALEFFO scores increased progressively with increasing number of VFX, especially lumbar fractures (p < 0.001). Patients with a single VFX already had a significant increase in QUALEFFO scores (p < 0.05). Similar, though weaker, associations were seen for NHP and EQ-5D scores. This study confirms decreased HRQOL for patients with prevalent VFX. In osteoporotic patients, QUALEFFO scores change in relation to the number of VFX. QUALEFFO is suitable for clinical studies in patients with postmenopausal osteoporosis.